Nasionalisme dan revolusi di Malaysia dan Indonesia pengamatan sejarah - Abdul Rahman Haji Ismail; Azmi Arifin; Nazarudin Zainun (Siri kecetakan akademik / Penerbit USM, 2006)
Historical viewpoint on nationalism, revolutions, and political development in Malaysia and Indonesia in the 20th century; collection of articles.